(untitled) (Journal of Human Sciences, 2021)
The article presents an approach to post-crisis management in educational institutions through the example of post-suicide psychological crisis. That is, what should educational actors, in cooperation with their external partners, do to mitigate the impact of the trauma of losing a member of the educational family? How can we return as soon as possible to the former stability and reduce the negative effects of the crisis on the Learning Act and on the ability to adapt to life’s changes? The article is divided into two parts: In the first section, I described and evaluated the experience of the counsellor in guidance in Tunisia, in his field work in collaboration with several partners, in escorting pupils with difficulties, especially after a colleague’s suicide crisis. Explain the legal framework provided by the Ministry of education in Tunisia for such interventions. However, these attempts have remained tentative and lack a strategy that would elevate it to crisis management. Therefore, I see the need to develop them by analyzing the experiences of countries with better quality educational systems, such as Canada. In a second section, she presented a structuring of the Quebec Suicide Prevention Association’s Canadian approach to post-crisis management. By identifying the actors, and the goals set in each situation: from the declaration of suicide to the reactions of loss or mourning. This approach is not to be copied, but to be used to devise, test and develop crisis management schemes in the educational systems of our Arab countries in order to protect them from shocks effects that disrupt their educational function. Conclusions and recommendations were formulated aimed at deepening research into educational crisis management.